Preparation of BiOCl/Bi2WO6 Photocatalyst for Efficient Fixation on Cotton Fabric: Applications in UV Shielding and Self-Cleaning Performances - Jiayi Chen (MDPI AG, 2021)
In this work, a visible-light-driven BiOCl/Bi2WO6 photocatalyst was obtained via a facile hydrothermal method and characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive spectrometry (EDS), X-ray photoelectron spectroscopy (XPS), ultraviolet/visible light diffuse reflection spectroscopy (UV/Vis), and photocurrent (PC). BiOCl/Bi2WO6 was modified with (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride to obtain the cationized BiOCl/Bi2WO6. Cotton fabric was pretreated with sodium hydroxide (NaOH) and sodium chloroacetate solution to obtain carboxymethylated cotton fabric, which was further reacted with cationized BiOCl/Bi2WO6 to achieve finished cotton fabric. The cotton fabrics were characterized by Fourier-transform infrared spectroscopy (FT-IR), XRD, SEM, and EDS. The photocatalytic activity of the BiOCl/Bi2WO6 photocatalyst and cotton fabrics was assessed by photocatalytic degradation of MB (methylene blue) solution under simulated visible light. The self-cleaning property of cotton fabrics was evaluated by removing MB solution and red-wine stains. Results revealed that the coated cotton fabrics exhibited appreciable photocatalytic and self-cleaning performance. In addition, anti-UV studies showed that the finished cotton fabrics had remarkable UV blocking properties in the UVA and UVB regions. Therefore, the finished cotton fabric with BiOCl/Bi2WO6 can provide a framework for the development of multifunctional textiles.